Phosphate abatement using calcium silicate hydrate synthesized from alum factory solid waste residue. Issue 11 (24th July 2022) - Gizaw, Alemu; Zewge, Feleke; Chebude, Yonas; Tesfaye, Melakuu; Mekonnen, Andualem
ABSTRACT: Calcium silicate hydrate (CSH), synthesized from the solid waste residue (SWR) of Awash Melkassa Alum Factory was examined for phosphate removal from an aqueous solution. The synthesized CSH was characterized using BET surface area analyzer, Scanning Electron Microscopy, Powder X-ray diffraction, and Fourier-transform infrared spectroscopy. Response surface methodology (RSM) adapted to assess a model equation that correlates the phosphate removal efficiency (R %) with the factors affecting adsorption such as initial phosphate concentration (Co ), adsorbent dosage, pH, and time (t). Optimum removal efficiency of 95.69% attained at Co  =5.5 mg/L, dose = 5 g/L, pH = 5, and t = 90 min at which consecutive experiments conducted. The adsorption kinetics experimental data fitted well to both pseudo-second-order model (R 2  = 0.999) and Elovich model (R 2  = 0.996) imply that chemisorption is dominant adsorption mechanism for phosphate adsorption on CSH. The isotherm experimental data fitted well to the Langmuir model (R 2  = 0.965). The maximum phosphate adsorption capacity (qm ) of 82.58 mg/g obtained at 45°C. The attained negative standard free energy (ΔG o  = −5.18 kJ/mol) and positive enthalpy (ΔH o  = 7.10 kJ/mol) confirms the spontaneity and endothermic nature of phosphate adsorption by CSH. The synthesized CSH tested for its phosphate removal (R = 63.78%) using real wastewater collected from a local wastewater treatment plant. Bicarbonate and sulfate observed to compete for active sites on the adsorbent during phosphate removal. Generally, the synthesized CSH can be considered as a low-cost silicate material for phosphate abatement. GRAPHICAL ABSTRACT: uf0001